Perencanaan Jalur Sepeda Sebagai Tujuan Wisata Desa Di Kecamatan Payangan, Kabupaten Gianyar - MAHAYANA, IDA BAGUS SURYA; MAYUN, IDA AYU; ASTININGSIH, ANAK AGUNG MADE (Jurnal Arsitektur Lansekap, 2016)
ABSTRACT Bike Path Planning as a Tourist Destination Village in the District of Gianyar Payangan Regency Payangan District has potential good attractiveness to the develope. Some of a district in the villages, dont have tourism accomodation yet. Developed alternative is cycling. This cycle way is needed to optimalize all the potential tourism industry in the villages. This cycle way concept is doing by approach and concideing of potential wich has been existing in order to creased tourism industry. Does cycle way are present 1) potential in each village, 2) the passing way each village, 3) tourism industry, 4) group of tourism, 5) tourism production, 6) a circulation concept.